A burning question: What experimental heating of Australian fauna can tell us about cooking practices in Boodie Cave, Barrow Island, northwest Australia. (August 2022) - Moody, Kate; Ristovski, Nikola; Manne, Tiina; Ward, Ingrid; Veth, Peter
Highlights: Bones from Australian fauna are heated in hearth fires, earth ovens and a kiln. Burning characteristics are found to be generally comparable to those of other taxa. The causes of heated bone at Boodie Cave, northwest Australia are examined. Burned bone analysis provides insights in the absence of any combustion features. Abstract: Burning characteristics of bone are dependent on taxa, bone condition, and heating method. Until now, heating characteristics of Australia's unique fauna were undocumented. Here we present heating experiments of Australian taxa using a laboratory kiln, hearth fires and earth ovens, and apply the results to faunal assemblages from Boodie Cave, northwest Australia. Results indicate comparable burning characteristics in Australian faunal bone to previous experimental research, with clear differences in the temperature at which burning characteristics occur between taxa and in particular marine and terrestrial fauna. Earth oven cooking causes very limited burning of the extremities of faunal bones, whilst hearth fires produce a high degree of non-uniform calcination and fracturing. In the Boodie Cave assemblage, low levels of heating throughout the deposit are consistent with post-depositional burning and fleshed cooking, though the exact heating process remains unclear in the absence of any identified combustion features.